2022
DOI: 10.1038/s41588-022-01172-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved pea reference genome and pan-genome highlight genomic features and evolutionary characteristics

Abstract: Complete and accurate reference genomes and annotations provide fundamental resources for functional genomics and crop breeding. Here we report a de novo assembly and annotation of a pea cultivar ZW6 with contig N50 of 8.98 Mb, which features a 243-fold increase in contig length and evident improvements in the continuity and quality of sequence in complex repeat regions compared with the existing one. Genome diversity of 118 cultivated and wild pea demonstrated that Pisum abyssinicum is a separate species diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 142 publications
1
62
0
Order By: Relevance
“…A unique feature of our study was the use of ultralong nanopore reads for creating manually curated scaffolds for most of the assembly, since the repetitive and complex structure of pea centromeres makes them prone to misassemblies. This makes our CEN6 assembly superior in completeness and contiguity even to the novel high-quality genome assembly of the pea cultivar ZW6 (Yang et al 2022) (data not shown), which was published during preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 96%
“…A unique feature of our study was the use of ultralong nanopore reads for creating manually curated scaffolds for most of the assembly, since the repetitive and complex structure of pea centromeres makes them prone to misassemblies. This makes our CEN6 assembly superior in completeness and contiguity even to the novel high-quality genome assembly of the pea cultivar ZW6 (Yang et al 2022) (data not shown), which was published during preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 96%
“…A unique feature of our study was the use of ultralong nanopore reads for creating manually curated scaffolds for most of the assembly, since the repetitive and complex structure of pea centromeres makes them prone to misassemblies. This makes our CEN6 assembly superior in completeness and contiguity even to the novel high-quality genome assembly of the pea cultivar ZW6 [ 27 ], which was published during preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…The OsAILs protein sequences were obtained from the Rice Genome Annotation Project ( ) and National Center for Biotechnology Information ( ). The GmAILs and LjAILs protein sequences were obtained in Phytozome, and the PsAILs protein sequences were obtained in the Pea Genome Database ( ) ( Yang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%